Tranformasi Pendidikan Di Era Digital - Sindi Septia Hasnida; Ridho Adrian; Nico Aditia Siagian (Jurnal Bintang Pendidikan Indonesia, 2024)
Digital transformation has changed the paradigm in the world of education, having a significant impact on learning and teaching methods. This article discusses key aspects of this transformation, such as greater information accessibility, the development of 21st century skills, digital literacy, and various forms of online, distance, personalized and lifelong learning. Digital assessments have also become an important element in measuring student progress. This transformation not only brings opportunities, but also challenges that require collaboration, innovation and interesting learning experiences. The importance of understanding the implications of digital transformation in the world of education is emphasized to face rapid technological changes. The research method used is library research which comes from books and journals, so that the truth can be verified. Technological advances will bring many changes, information will arrive very quickly, learning will be easy to do, making interaction easier.